RMB Internationalization - Ao, Xiying (2011)
An International currency refers to a currency that could be used outside of its issuing country as a unit of account, a medium of exchange and a store of value. On the one hand, currency internationalization could stimulate nancial business in domestic banks and seignorage, enhance the political power and prestige of the issuing country, and benet domestic residents in trading and investment. On the other hand, a currency, once internationalized, cannot be completely controlled by the issuing country through any kind of monetary policy, which signicantly complicates the policy-making process. Four important factors aecting international use of a currency, including the economic power, level and variability of ination, uctuation of exchange rate of the issuing country and the status of its nancial market development. This dissertation aims to build up the concept of a three-stage currency internationalization process, assess the current status of RMB internationalization and develop the strategies to enhance levels of RMB internationalization at dierent stages. Key words: Currency Internationalization, RMB, Internationalization Policy, Internationalization Strategy